Sicily and Italy in the Odyssey - Currie, B (L'Erma Di Bretschneider, 2020)
The article reviews the arguments for seeing ‘Temese’ (Od. 1.184) and ‘Alybas’ (24.304) as Italian place names, and considers the significance of the Odyssey’s being bookended by putative references to fictitious voyages to and from Italy by ‘Mentes’ and ‘Eperitos’ respectively. Sicilians, moreover, cut intriguingly different figures in the poem. On the one hand, the Suitors think of Sicilians as ruthless slave-dealers (20.383). On the other, Laertes relies on a devoted Sicilian woman (24.211-12), and Odysseus pretends to a fervent guest-friendship with a man from Sicania (24.303-14). The positive attitude of Odysseus and Laertes (and, by implication, of the poem’s narrator and narratee) towards Sicilians contrasts very suggestively with the negative attitude of the Suitors. It is, finally, suggested that Odysseus’ encounters with monsters and man-eaters (the Cyclopes, the Laestrygonians, Skylla and Charbdis, Kirke) may already have been situated in Sicily and Italy prior to the Odyssey, and that the poet of the Odyssey purposely refrained from situating his monsters there. Thus the Odyssey-poet himself may have pointedly adopted a positive attitude to the heroic-age inhabitants of Sicily that contrasted with the negative attitude prevailing in his tradition. This putative decision not to demonize the inhabitants of Sicily may be the natural concomitant of a desire to show the home-grown Suitors of Ithaca as the real “monsters” of the Odyssey.